2020
DOI: 10.3389/fimmu.2020.569524
|View full text |Cite
|
Sign up to set email alerts
|

The Long Non-coding RNAs: Paramount Regulators of the NLRP3 Inflammasome

Abstract: The NOD LRR pyrin domain containing protein 3 (NLRP3) inflammasome is a cytosolic multi-proteins conglomerate with intrinsic ATPase activity. Their predominant presence in the immune cells emphasizes its significant role in immune response. The downstream effector proteins IL-1β and IL-18 are responsible for the biological functions of the NLRP3 inflammasome upon encountering the alarmins and microbial ligands. Although the NLRP3 inflammasome is essential for host defense during infections, uncontrolled activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 209 publications
0
31
0
Order By: Relevance
“…Serological tests show that the inflammatory cytokine storm response (ICSR) is associated with COVID-19 severity and mortality as a result of an uncontrolled systemic inflammatory response in the host (4,(64)(65)(66). IL-6 and NLRP3 inflammasome complexes are the main immune components of the immune response after pathogen infection, and their function and expression are significantly affected by ncRNAs, including lncRNAs (44,67,68). IL-6, which is a typical proinflammatory factor causing cytokine storm, seems have a direct association with a worsened patient condition, is particularly affected (69,70).…”
Section: Inflammatory Responsementioning
confidence: 99%
“…Serological tests show that the inflammatory cytokine storm response (ICSR) is associated with COVID-19 severity and mortality as a result of an uncontrolled systemic inflammatory response in the host (4,(64)(65)(66). IL-6 and NLRP3 inflammasome complexes are the main immune components of the immune response after pathogen infection, and their function and expression are significantly affected by ncRNAs, including lncRNAs (44,67,68). IL-6, which is a typical proinflammatory factor causing cytokine storm, seems have a direct association with a worsened patient condition, is particularly affected (69,70).…”
Section: Inflammatory Responsementioning
confidence: 99%
“…MALAT1 also exerts various immunological effects including the mediation of NLRP3 inflammasome activation. ( Menon and Hua, 2020 ; Yu et al, 2018 ) MALAT1 has been linked to M1-like activity in macrophages, promoting inflammation. ( Cui et al, 2019 ) Our finding that MALAT1 is overexpressed in BAL MoMa of severe versus mild patients suggests that it might be involved in precipitating a shift towards M1 macrophages that exacerbates inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been shown to regulate the occurrence and development of in ammatory diseases 35,36 . Maninjay K et al found that LINC-EPS regulated in ammatory response at the transcriptional level, inhibiting in ammation progression 37 .…”
Section: Discussionmentioning
confidence: 99%